Efficacy and acceptability of varenicline for alcoholism: A systematic review and meta-analysis of randomized-controlled trials - Awirut Oon-arom (2020)
© 2019 Elsevier B.V. Background: Current pharmacological treatment for alcoholism remains unsatisfactory. While there have been several clinical trials investigating the efficacy and safety of the therapeutic use of varenicline in alcoholism, no definitive review of this topic has been carried out. This systematic review aimed to determine the efficacy and acceptability of the use of varenicline in treating alcoholism. Methods: This systematic review included double-blinded, randomized, placebo-controlled trials reporting heavy drinking days, amount of alcohol consumption, overall dropouts, or dropouts due to adverse events. We searched PubMed, Scopus, Web of Science, ClinicalTrials.gov, and the Cochrane Library in January 2019. We independently selected the trials and assessed the quality of included studies. We calculated standardized mean differences on heavy drinking days and the amount of alcohol consumption. We calculated the relative risks for dropout rate. All data were pooled using random-effects models. Result: This systematic review included nine double-blind, randomized, placebo-controlled trials (N = 585). The study duration ranged from 4 to 13 weeks. Varenicline therapy was not superior to placebo in decreasing heavy drinking days but significantly superior to placebo in decreasing alcohol consumption. There were no statistically significant differences between groups on dropout rates due to any reason or due to adverse events. Conclusion: Varenicline therapy is effective in decreasing alcohol consumption over a period of time. It may be an option for decreasing heavy drinking days in patients with alcoholism. It is a well-accepted medication for alcoholism. More studies are needed to determine if varenicline is effective in decreasing heavy drinking.